(untitled) (Global Journal of Human-Social Science, 2023)
The purpose of this study was to examine the determinants of students choice of program at the Senior High School SHS level in the Gomoa East District of the Central Region of Ghana It was a quantitative study underpinned by the positivist paradigm The descriptive survey design was employed for the study A self-developed questionnaire was used to collect data from a sample of 229 for the study